Plant responses to warming and increased precipitation in three categories of dune stabilization in northeastern China. Issue 6 (21st August 2017) - Luo, Yongqing; Zhao, Xueyong; Zuo, Xiaoan; Li, Yuqiang; Wang, Tao
Abstract: Rising temperatures and precipitation are important climate change processes around the world. The responses of plants to these trends are still unclear in semi‐arid regions, especially in areas with degraded sandy grassland. To provide insights into the response in these regions, we investigated responses of vascular plants to warming and increased precipitation in mobile dunes, fixed dunes and grassland, which represent the series of sand dune stabilization by plants in semi‐arid northeastern China. Plant biomass, especially the aboveground biomass, varied significantly ( P < 0.05) among dune categories. Total plant density in the fixed dunes and grassland was 1.9 and 1.7 times that in the mobile dunes. Species richness differed slightly but significantly ( P < 0.05) among the habitats. Increasing precipitation in a drought year (65.5% of the long‐term average annual precipitation) by 30% did not significantly affect any plant variable. By contrast, warming significantly decreased the belowground biomass, total biomass, species richness and plant total density. In summary, in semi‐arid region with sandy soil, additional precipitation slightly improved plant performance, but increased temperature decreased plant performance. Soil texture, which determines the balance between moisture retention and evaporation, may be a key factor in determining these responses when precipitation is unusually low.